La lettera « Famuli uestrae pietatis » di Gelasio di Roma all'imperatore Anastasio I (CPL 1667, Ep. 8) - Ronzani, Rocco (Augustinianum, 2011)
The Gelasian letter, Famuli uestrae pietatis, addressed to Emperor Anastasius I (491-518), is famous for the so-called theory of two powers that has enjoyed considerable fortune and has received continual attention in the history and thought of the Latin West in view of its arguments about the relationship between the Church and secular power. Scholars have been primarily interested in the Wirkungsgeschichte of the letter. Less frequently studied is the letter's specific religious context, characterized by the Acacian schism (484- 519), the dispute between the episcopal sees of Rome and Constantinople. This article seeks to situate this document from the late fifth-century Roman pontifical chancery in its specific historical and ecclesial context, and to provide a commentary on the entire letter. A brief, final chapter offers a synthetic excursus on the immediate reception of the text in the Early Middle Ages before the Gregorian Reform.